Potentials of earthworm and its by-products in animal agriculture and waste management - A review (Bangladesh Journal of Animal Science, 2016)
A review work was conducted to unveil the potentials of earthworm (EW) and its by products such as earthworm meal (EWM) and earthworm casts (EWC) in poultry nutrition and management of animal waste. Production of EW is called vermiculture and using it to decompose organic matter is vermicomposting while processing it into such product as EWM is known as vermitechnology. Being a hermaphrodite, breeding is simple and fast, requiring only two EW to come together irrespective of their sexes. Fresh EW could be fed to fish and chickens. Based on literature EWM is high in protein 62 to 65%, essential amino acids such as lysine 6 to 8%, methionine 2 to 5%, leucine 8 to 10%, isoleucine  4 to 6% and phenylalanine 4 to 6%; fat 5 to 8% and fibre< 8%. At dietary inclusion level of 0.2 to 0.6%, EWM reportedly increased feed intake, supported growth, improved carcass quality in broiler chickens, and marginally increased egg size and hen day in layers. Dry EWC could replace 5 to 10% maize in diet for finishing broiler chickens. Rich in macro plant nutrients (e.g. nitrogen 1.94%, calcium 4.4% and potassium 0.7%) EWC is nutritionally sound for growth of pasture crops especially legumes. Earthworm has cellulase, lichenase, chitinase and cellulolytic microorganisms which enable it to degrade organic waste. Cattle dung and other animal manure can be degraded by earthworm thereby reducing environmental pollution. In this era of organic farming and sustainable environment, EW could therefore have a potential place in animal nutrition and management of waste from animals.Bang. J. Anim. Sci. 2016. 45 (2): 1-9